Initial handgrip strength as a predictive factor for amputation risk in diabetic foot patients - İMRE, EREN (My University, 2024)
BackgroundWe aimed to analyze the prognostic significance of handgrip strength as predictor of lower extremity amputation at 1year follow up in patients with type 2 diabetes.MethodsWe evaluated 526 patients with type 2 diabetes between August 2020, and, June 2022. We collected from the electronic medical records demographic variables, laboratory data and history of amputation. The handgrip strength was assessed using a handheld Smedley digital dynamometer following the NHANES Muscle Strenght/Grip Test Procedure. Low handgrip strength was defined for women as less than 16kg and for men less than 27kg. Outcome variable was major or minor lower extremity amputation.ResultsA total of 205 patients with complete data entered the study. Patients mean age was 59 years old, 37% were women and the mean diabetes disease duration was 14 years. Seventy-seven (37%) patients suffered from lower extremity mputations (26 major and 51 minor amputations). After controlling for age, gender, presence of peripheral artery disease, body mass index and white cell counts as confounder variables, patients with low handgrip had an increased risk for amputations (Odds Ratio 2.17; 95% confidence Interval: 1.09–4.32; <0.001).ConclusionLow handgrip stregth is an independent prognostic marker for lower limb amputation at one year in patients with diabetes.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENDOKRİNOLOJİ VE METABOLİZMA; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; ENDOCRINOLOGY & METABOLISM; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Endokrin ve Otonom Sistemler; Dahiliye; Aile Sağlığı; Endokrinoloji, Diyabet ve Metabolizma; Tıp (çeşitli); Genel Tıp; Endokrinoloji; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Endocrine and Autonomic Systems; Internal Medicine; Family Practice; Endocrinology, Diabetes and Metabolism; Medicine (miscellaneous); General Medicine; Endocrinology; Life Sciences